José Moret, chronicler of the Kingdom of Navarre and his knowledge about the auxiliary sciences of the History - Ostolaza Elizondo, Isabel (Huarte de San Juan. Geografía e Historia, 2017)
The author reviews the intellectual biography of José Moret, chronicler of Navarre and his relationship with the institutions of the kingdom (Cortes, Viceroy, Council of Navarre). She focuses on his facet of professional historian: training, methodology, mastery of the auxiliary sciences. Through his printed and handwritten works she analyzes the archives and chronicles he consulted. She identifies some of the books that made up his library. Finally, she details two cases in which he was consulted to issue reports on medieval documents.
Keywords: José Moret; chronicler of Navarre; genealogy; archives; historiography